Implementasi Manajemen Strategik Shopee dalam Ekosistem E-Commerce - Firmansyah .; Titin Suherti (Jurnal Ekonomi dan Bisnis Digital, 2026)
The rapid growth of the digital economy has intensified competition in Indonesia’s e-commerce industry, requiring companies to implement adaptive and innovative strategic management. This study aims to analyze the implementation of strategic management within the e-commerce ecosystem using a case study of Shopee. The research employs a descriptive qualitative approach through literature review and documentation based on secondary data from industry reports, academic journals, and official publications. The findings indicate that the company’s strategic success is supported by an integrated digital ecosystem encompassing marketplace services, logistics, digital payments, and continuous application innovation that enhances user experience and customer loyalty. Empirically, Indonesia’s e-commerce market, with a GMV reaching approximately USD 62 billion and supported by more than 215 million internet users, provides significant strategic opportunities leveraged through market penetration strategies, digital promotions, and technology-based differentiation. The implementation of strategic management oriented toward innovation, user data utilization, and service integration strengthens competitive advantage and market positioning in a dynamic digital environment. Therefore, adaptive, customer-centric, and technology-driven strategies are essential for sustaining competitiveness and long-term growth in the digital economy.